Description of a new species of Phymastichus (Hymenoptera: Eulophidae), a parasitoid of adult shothole borers Euwallacea spp. (Coleoptera: Curculionidae) in Asia - Husein, Deena; Triapitsyn, Serguei V.; Liu, Fang-Ling; Liao, Yi-Chang; Dodge, Christine E.; Tuan, Shu-Jen; Stouthamer, Richard; Rugman-Jones, Paul F. (Journal of Asia-Pacific entomology, 2025)
[Display omitted] •New species of Phymastichus described.•Endoparasitoid of adult members of the Euwallacea fornicatus species complex.•Potential classical biological control agent. Phymastichus nudusdraco Triapitsyn & Rugman-Jones, sp. n. (Hymenoptera: Eulophidae: Tetrastichinae) is described and illustrated based on the type series from Taiwan and reared specimens from quarantine colonies of Taiwan origin. This species, which is also known from Thailand, is a solitary parasitoid of adult shothole borers Euwallacea spp. (Coleoptera: Curculionidae: Scolytinae) in Asia. In Taiwan, its confirmed hosts are E. fornicatus (Eichhoff) and E. kuroshio Gomez & Hulcr, and as such, in the USA it is being evaluated under quarantine conditions as a potential classical biological control agent against these two invasive species in southern California. In Thailand, the known host of P. nudusdraco is a third shothole borer species, E. perbrevis (Schedl), which has invaded the U.S. states of Florida and Hawaiʻi. Unambiguous supporting molecular evidence for separation of the four named species of the genus Phymastichus LaSalle is provided. Although there is a slight but consistent difference in the coloration of legs in female P. nudusdraco specimens from Taiwan and Thailand, genetically, these are sufficiently similar to confirm conspecificity.